Answer:
3
Step-by-step explanation: you would use PEMDAS parenthesis, exponents, multiply, division, add, subtract. First you multiply 3 times 2 and get 6 plus 5 is 11 lastly you minus 11 with 8 and get 3
Answer:
Step-by-step explanation:
4x + 3y = 6 -----------------(I)
4x - y =2 ---------------------(II)
Multiply (II) by (-1) and then add
(I) 4x + 3y = 6
II) *(-1) <u> - 4x + y = - 2 </u> {Now add, x will be eliminated}
4y = 4
y= 4/4
y= 1
Plugin y =1 in equation (I)
4x +3*1 = 6
4x + 3 = 6
4x = 6- 3
4x = 3
x = 3/4
2 to the 2nd power times 3 to the second power times 5
4 X 9 X 5 = 36 X 5 = 180
so the answer is 180
hope this helps
Answer:
-5, -2, -1, 2
Step-by-step explanation:
You can find the answer by trying the given possible answers out.